Selenium Deficiency Exacerbates Hyperoxia-Induced Lung Injury in Newborn C3H/HeN Mice - Lora C. Bailey-Downs; Laura G. Sherlock; Michaela N. Crossley; Aristides Rivera Negron; Paul T. Pierce; Shirley Wang; Hua Zhong; Cynthia Carter; Kathryn Burge; Jeffrey V. Eckert; Lynette K. Rogers; Peter F. Vitiello; et al. (MDPI AG, 2024)
Extremely preterm infants are often treated with supraphysiological oxygen, which contributes to the development of bronchopulmonary dysplasia (BPD). These same infants exhibit compromised antioxidant capacities due in part to selenium (Se) deficiency. Se is essential for basal and inducible antioxidant responses. The present study utilized a perinatal Se deficiency (SeD) mouse model to identify the combined effects of newborn hyperoxia exposure and SeD on alveolarization and antioxidant responses, including the identification of affected developmental pathways. Se-sufficient (SeS) and SeD C3H/HeN breeding pairs were generated, and pups were exposed to room air or 85% O2 from birth to 14 d. Survival, antioxidant protein expression, and RNA seq analyses were performed. Greater than 40% mortality was observed in hyperoxia-exposed SeD pups. Surviving SeD pups had greater lung growth deficits than hyperoxia-exposed SeS pups. Gpx2 and 4 protein and Gpx activity were significantly decreased in SeD pups. Nrf2-regulated proteins, Nqo1 and Gclc were increased in SeD pups exposed to hyperoxia. RNA seq revealed significant decreases in the Wnt/β-catenin and Notch pathways. Se is a biologically relevant modulator of perinatal lung development and antioxidant responses, especially in the context of hyperoxia exposure. The RNA seq analyses suggest pathways essential for normal lung development are dysregulated by Se deficiency.